Art geeks and prom queens - Noel, Alyson (New York : St. Martin's Griffin, 2005)
Seventeen-year-old Alex seriously messes up during her senior year at an Orange County, California high school, skipping classes and staying out all night at Hollywood night clubs with older guys, in an effort to distract herself from some unpleasant realities.
1 3 11 16
Keywords: Interpersonal relations -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction; Los Angeles (Calif.) -- Fiction